KELAYAKAN SCRAPBOOK SUB MATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA - Herlenda Herlenda; Syamswisna Syamswisna; Reni Marlina (FKIP Universitas Tanjungpura, 2020)
This research aimed to determine the feasibility of using scrapbook in teaching sub-topic of biodiversity in Indonesia. The type of research was descriptive qualitative research. The determination of the validator was obtained through purposive sampling. The scrapbook education media was validated by two lecturers of Biology Education Study Program at Tanjungpura University and three Biology teacher of grade X at three schools in Simpang Hilir District. The scrapbook media was validated based on three aspects: format, content and language. Based on validator's assessment which was analysed using , the scrapbook was categorized in the valid category with a calculated CVI value of 1.00 so that it is appropriate to be used as a learning media on the sub-material utilization of Indonesian biodiversity.